The Politics of Epistemology - Reed, Cassandra (Stance: an international undergraduate philosophy journal, 2019)
This paper focuses on the metaphysical and conceptual structures of reality organization that exist currently in western culture. Taking a feminist perspective, this paper analyzes how some disfavored social groups actively have their identities manipulated and sometimes conceptually erased from the dominant conceptual scheme. Utilizing this analysis, it is concluded that this conceptual scheme perpetuates oppression; therefore, maintained loyalty to it is incompatible with the belief that all people should be treated as full persons.